The Study Of Path Planning For A Perpetual Solar Powered Flight Across Regions Around The World - Tan, Chin How (Universiti Sains Malaysia, 2017)
Perpetual flight of solar power UAV on same location has been achieve in recent researches. If the perpetual flight of solar power UAV is change into worldwide instead on same location, it can be a pseudolite, function as a part of communication satellite. It will be cheaper and easier to launch for those countries still under development. In order to achieve the perpetual flight, the power supply play important role. Since it is solar powered UAV, it able to collect energy from sunlight during day time and store up the excessive energy into battery for the power consumption during night time. The amount of energy available in night time must sustain the flight, which are manipulated by the capacity of battery, total energy collected and energy consumption rate. The total energy collected is highly depend on intensity of solar irradiance. In the recent researches, a lot of study on UAV has been done in order to increase the performance in term of endurance. Researches on path planning of UAV are available but limited to surveillance missions, target tracking and real time autonomous path planning. The data of worldwide solar irradiance intensity for each hour is required in order to plan a delicate flight path and achieve perpetual flight. In this paper, the worldwide solar irradiance intensity and digital elevation will be collected and used in Matlab programming software. Matlab programming software is used to identify the possibility of perpetual flight across region around the world. The battery status along the flight paths will identify and analyse. It also expected the UAV signal coverage will cover every region on earth. The path planning result shown that flight pattern A and B both have the possibility to achieve perpetual flight. But flight pattern A have higher risk and restriction than flight pattern B. The parameters with high impact have discussed in this thesis and recommended range are suggested.